Additive prognostic value of cardiac biomarkers in patients with chronic obstructive pulmonary disease and heart failure. (14th October 2021) - Aimo, A; Vergaro, G; Januzzi, J; Richards, A.M; Lam, C.S.P; Latini, R; Bayes-Genis, A; Brunner-La Rocca, H.P; De Boer, R; Ueland, T; Gaggin, H.K; Anand, I; et al.
Abstract: Background: Chronic obstructive pulmonary disease (COPD) is a frequent comorbidity in patients with heart failure (HF). We assessed the influence of COPD on circulating levels and prognostic value of 3 HF biomarkers: N-terminal pro-B-type natriuretic peptide (NT-proBNP), high-sensitivity troponin T (hs-TnT), and soluble suppression of tumorigenesis-2 (sST2). Methods: Individual data from patients with chronic HF, known COPD status and NT-proBNP, hs-TnT, sST2 values (n=13328) were analysed. Results: As compared to patients without COPD, those with COPD (n=2155, 16%) were older (age 71 years [64–77] vs. 66 [57–75]; p<0.001), more frequently men (79% vs. 74%; p<0.001), had more severe dyspnoea (43% in New York Heart Association [NYHA] class III-IV vs. 31%; p<0.001), slightly worse renal function (median estimated glomerular filtration rate [eGFR] 58 mL/min/1.73 m 2 [43–73] vs. 60 [46–77]; p<0.001), higher NT-proBNP (1508 ng/L [650–3363] vs. 1239 ng/L [479–2911]; p<0.001), hs-TnT (22 ng/L [13–38] vs. 17 ng/L [9–30]; p<0.001), and sST2 (31 ng/mL [23–45] vs. 29 [21–43]; p=0.040). In both the COPD and no-COPD subgroups, the best cut-offs of the 3 biomarkers refined the prediction of 1- and 5-year all-cause and cardiovascular mortality and 1- to 12-month HF hospitalization over a prognostic model including age, sex, ischemic aetiology, eGFR, HF categories, NYHA III-IV, beta-blocker use and the NT-proBNP cut-off alone. Conclusions: Among patients with HF, those with COPD have higher circulating cardiac biomarkers. Patient classification based on COPD-specific cut-offs refines risk reclassification for all-cause and cardiovascular mortality and HF hospitalization and might be helpful for decision making and management. Funding Acknowledgement: Type of funding sources: None.